Development of MeJiKuHiBiNiUn Creative Learning Video Media In Mathematics Subject In Grade V Elementary School - Ahmad Rustam; Agnes Nogo Temu; Ashari Usman (JME (Journal of Mathematics Education), 2022)
The digital era is  a time when technological developments occur in all parts of the world. As a society that lives in this digital era, we should fallow the current technological developments that we feel. Utilizing technology to solve the problems in the world of education is a wise action. One of the uses of technology in education is to use creative learning video media based on computer technology using the powtoon aplication. The purpose of this research is to develop creative learning video media. The method used is the research and development method in class V SD Negeri 84 Kendari, using the DDD- E method. The data analysis technique used the analysis technique of validation result and the analysis technique of the questionnaire responses of teachers and students. It can be concluded that this creative learning video media MeJiKuHiBiNiUn feasible to be use in the learning process in the fifth grade of elementary school.